Bikatech Sdn. Bhd. : Portable Bike Rack / Dzul Hakim Zahir...[et al.] - Zahir, Dzul Hakim; Rofie, Muhammad Suhail; Mohd. Nasir, Muhammad Syafiq; Ridzuan, Muhammad Akmal; Amran, Muhammad Aiman (2016)
It is expected that our business will progress further and become more profitable in the long run. We strive to become the best company for this product as it has more potential to be innovated in the near future, so the demand will increase as well.